Evaluation of a Transition to University Programme for Students with Autism Spectrum Disorder - Lei, Jiedi (J Autism Dev Disord, 2018)
Applying to university can be an anxiety-provoking time for many autistic students, though enrolment can be increased by actively involving them in transition planning. We provide an evaluation of a transition to university pilot programme (Autism Summer School) for autistic students (16–19 years) who are seeking to apply/attend university. The content focused on introducing students to various aspects of university life including academic (sample lectures), social (e.g., clubs and societies), and daily living (eating in university canteen and staying in student accommodation). Students’ quantitative and qualitative feedback are positive and promising, showing significant reduction across a range of concerns related to transition to university after the programme, as well as general optimism related to starting university.